2021
DOI: 10.1002/vnl.21816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of chitosan with halloysite nanotubes on the properties of polylactic acid hybrid biocomposites

Abstract: In this study, hybrid chitosan/halloysite nanotubes (Cs/HNTs) reinforced polylactic acid (PLA) were prepared via melt compounding and compression molding techniques. In the fabrication of PLA/Cs/HNTs hybrid biocomposites, the partial replacement of Cs with HNTs was performed at filler loading of 2.5 parts per hundred parts of polymer (php), proceeding from the highest tensile strength of PLA/Cs obtained in our previous study. Cs was partially replaced with different HNTs loadings (0.5, 1, 1.5, 2, and 2.5) php … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Additionally, the major degradation step was presented at 200-380 C, which represented approximately ~93%-98% of weight losses. This was ascribed by the simultaneous degradation of PLA molecules and the breakdown of saccharide structure of Cs component as stated in the study reported by Kamaludin et al 57 The degradation of carbonaceous residue occurred beyond 400 C.…”
Section: Thermogravimetric Analysismentioning
confidence: 67%
“…Additionally, the major degradation step was presented at 200-380 C, which represented approximately ~93%-98% of weight losses. This was ascribed by the simultaneous degradation of PLA molecules and the breakdown of saccharide structure of Cs component as stated in the study reported by Kamaludin et al 57 The degradation of carbonaceous residue occurred beyond 400 C.…”
Section: Thermogravimetric Analysismentioning
confidence: 67%
“…Bare and composite nanofibers showed C–O stretching vibration at 1375 cm –1 . , The peak at 1666 cm –1 was related to the −CC– bonds in the PAN structure. The stretching vibration of O–H on the inner surface of the HNT is related with the distinctive bands in the FTIR spectra of HNT at 3625 cm –1 . , The strong vibration band seen at 1000–1038 cm –1 can be attributed to the Si–O–Si bond originating from the HNT . Vibration bands seen at this wavenumber are not examined in the bare membrane but are measured in bare HNT powder and all of HNT composite nanofilters.…”
Section: Resultsmentioning
confidence: 99%